2007
DOI: 10.1111/j.1524-4725.2006.32330.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study Comparing the Diffusion of Two Formulations of Botulinum Toxin Type A in Patients with Forehead Hyperhidrosis

Abstract: BoNTA(2) has a greater area of diffusion in the forehead than BoNTA(1), even with identical injection volumes. This may hinder accurate localization of clinical effect, thereby increasing the potential for adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 14 publications
3
80
2
4
Order By: Relevance
“…This might not be a drug-related effect but could instead be due to variability of the clinical scoring method used, and this weakens the conclusions of Lowe and colleagues substantially. 23 According to a Phase II Food and Drug Administration trial of Dysport in the treatment of glabellar lines, a dosage of as low as 20 U is effective in most cases, supporting a unit equivalence of 2.5:1. , Karsai et al 21 , Monheit et al 24 , Ascher et al 26 , Rzany et al 29 , Ranoux et al 31 , Odergren et al 33 , Poewe et al 34 , Simonetta-Moreau et al 38 , Talarico-Filho et al 40 , Wohlfarth et al 43 IIa SR of cohort studies (CS) with homogeneity Sesardic et al 9 , Poewe, 32 Rosales et al 45 IIb Individual CS or low-quality RCT Bihari, 16 Lowe et al 22 , Brisinda et al 35 , Sampaio et al 36 , Nü Xgens and Roggenkä mper, 37 Trindade de Almeida et al 39 , Hexsel, 41 de Almeida et al 42 IIc ''Outcomes'' research Marchetti et al 17 , Heckmann and Schö n-Hupka, 25 Van den Bergh and Lison, 44 Rosales et al 45 V Expert opinion Hambleton and Pickett, 7 Rzany and Zielke, 11 Sommer et al 20 SR, systematic review; RCT, randomized controlled trial; CI, confidence interval; CS, cohort study.…”
Section: Cosmetic Applications (Hyperfunctional Lines)mentioning
confidence: 99%
See 1 more Smart Citation
“…This might not be a drug-related effect but could instead be due to variability of the clinical scoring method used, and this weakens the conclusions of Lowe and colleagues substantially. 23 According to a Phase II Food and Drug Administration trial of Dysport in the treatment of glabellar lines, a dosage of as low as 20 U is effective in most cases, supporting a unit equivalence of 2.5:1. , Karsai et al 21 , Monheit et al 24 , Ascher et al 26 , Rzany et al 29 , Ranoux et al 31 , Odergren et al 33 , Poewe et al 34 , Simonetta-Moreau et al 38 , Talarico-Filho et al 40 , Wohlfarth et al 43 IIa SR of cohort studies (CS) with homogeneity Sesardic et al 9 , Poewe, 32 Rosales et al 45 IIb Individual CS or low-quality RCT Bihari, 16 Lowe et al 22 , Brisinda et al 35 , Sampaio et al 36 , Nü Xgens and Roggenkä mper, 37 Trindade de Almeida et al 39 , Hexsel, 41 de Almeida et al 42 IIc ''Outcomes'' research Marchetti et al 17 , Heckmann and Schö n-Hupka, 25 Van den Bergh and Lison, 44 Rosales et al 45 V Expert opinion Hambleton and Pickett, 7 Rzany and Zielke, 11 Sommer et al 20 SR, systematic review; RCT, randomized controlled trial; CI, confidence interval; CS, cohort study.…”
Section: Cosmetic Applications (Hyperfunctional Lines)mentioning
confidence: 99%
“…A recent study analyzing the anhidrotic area in 20 patients with forehead hyperhidrosis 39 suggested a greater diffusion area of Dysport, possibly hindering the exact localization of the desired effect. As an ''accompanying result,'' the study failed to demonstrate differences in efficacy between both formulations at ratios of 2.5:1, 3:1, and 4:1, suggesting that a ratio of 2.5:1 is at least equipotent.…”
Section: Hyperhidrosismentioning
confidence: 99%
“…Im Hinblick auf das Diffusionsverhalten fand sich kein Unterschied zwischen Xeomin® und Botox® [22,28]. Zwischen den Komplexprotein enthaltenden Botox® (im Weiteren als BTX bezeichnet) und Dysport® hingegen zeigten sich im Halbseitenvergleich der anhidrotischen Areale der behandelten Stirn größere Diffusionsstrecken für Dysport® nach Applikation unterschiedlicher Dosisverhältnisse (1:2,5; 1:3; 1:4), aber gleicher Injektionsvolumina [27].…”
Section: Diskussionunclassified
“…In dieser Studie wurde jedoch nicht auf die Wirkdauer eingegangen. Im Halbseitenvergleich der Pilotstudie von Trinidade de Almeida et al [27] zeigte sich, dass eine geringere Diffusion des Botulinumtoxins z. T. mit einer stär-keren Hemmung der muskulären Aktivität einhergeht. Andere Studien hingegen sahen keine Unterschiede im paralytischen Effekt von Botulinumtoxin durch eine Veränderung der Verdünnungsvolu-mina [13,25].…”
Section: Einfluss Des Verdünnungs-bzw Injektionsvolumens Auf Die Wirunclassified
See 1 more Smart Citation